(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to investigate the effect of different response times for educational activities (time-limited vs. unlimited time) in a gamified e-learning environment on the development of programming skills among middle school students. The study used a quasi-experimental design. The sample consisted of 60 third-year middle school students from Al-Imam Al-Nawawi School, who were randomly assigned to two groups based on the response time model (time-limited vs. unlimited time). The results of the study showed a statistically significant difference at the 0.05 level in favor of the group that used the unlimited time response model, with an average score of 26.23 compared to the time-limited response group, which had an average score of 22.80. The calculated t-value (4.731) was greater than the critical t-value (1.98), indicating the superiority of the unlimited time response model in developing programming skills. The study recommended using time-unlimited activities in gamified e-learning environments, especially for teaching programming skills, to reduce anxiety caused by time pressure, and integrating interactive strategies based on digital games into the curriculum.